Customer Satisfaction Mediates Experience and Promotion in Online Travel Loyalty: Kepuasan Pelanggan Berperan sebagai Mediator antara Pengalaman dan Promosi dalam Program Loyalitas Perjalanan Online - Novita Wulan Ramadanti; Rusdi Hidayat Nugroho (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: The increasing competition among Online Travel Agent (OTA) platforms requires companies to understand factors associated with customer loyalty. Specific Background: Customer experience and digital promotion are considered important factors in shaping customer satisfaction and loyalty among Traveloka users. Knowledge Gap: Previous studies have reported inconsistent findings regarding the relationships among customer experience, digital promotion, customer satisfaction, and customer loyalty, while studies integrating these variables in the Indonesian OTA context, particularly among Traveloka users, remain limited. Aims: This study aims to analyze customer experience and digital promotion in relation to customer loyalty through customer satisfaction among Traveloka users in East Surabaya. Results: A quantitative approach was applied to 150 respondents using purposive sampling. Data were collected through questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 3. Customer experience and digital promotion showed positive and significant relationships with customer satisfaction and customer loyalty. Customer satisfaction also showed a positive and significant relationship with customer loyalty. The indirect effects of customer experience and digital promotion through customer satisfaction were significant, with coefficients of 0.182 and 0.191, respectively. Novelty: This study examines customer satisfaction as a mediating mechanism connecting customer experience and digital promotion with customer loyalty in the OTA industry. Implications: The findings provide empirical evidence for understanding loyalty formation among Traveloka users in East Surabaya and contribute to digital marketing and consumer behavior research. Highlights: All proposed direct relationships were statistically significant. The strongest coefficient for the intermediary construct was 0.440. The explanatory model accounted for 56.1% of variance in the outcome construct. Keywords: Customer Experience, Digital Promotion, Customer Satisfaction, Customer Loyalty, Traveloka.